Effectiveness of water extract of mangrove fruit flour (Rhizophora mucronata) as a natural preservative in skipjack fish fillets (Katsuwonus pelamis) - Maulanan, Risky S; Mile, Lukman; Djailani, Fernandy M. (Applied Environmental Science, 2025)
Background: Gorontalo is quite potential for the development of capture fisheries potential including the development of skipjack (Katsuwonus pelamis) production. In its processing, natural additives containing antimicrobial compounds are needed to preserve the fish. Rhizophora mucronata or R. mucronata is one type of mangrove that is widely spread along the tourist location "Tracking Mangrove" Langge Village, North Gorontalo Regency. This study aims to analyze the effect of length of storage of skipjack on organoleptic quality soaked using mangrove fruit water extract and analyze the effect of length of storage of skipjack on the quality of TPC and pH soaked using mangrove fruit water extract. Methods: This study uses a laboratory experimental method with 1 treatment, namely the length of soaking with 3 levels of treatment and 2 replicates, namely P1 (10-hour soaking), P2 (12-hour soaking), and P3 (14-hour soaking). The parameters tested were organoleptic, pH, and TPC. The research data were analyzed using a non-factorial Completely Randomized Design (CRD) with One-way ANOVA test with a significance level of 5% and further tested using Duncan. Finding: The results of the analysis showed that the best soaking time of skipjack in the solution mangrove fruit extract R. mucronata was found in P1 (soaking time of 10 hours) with indicators meat incision slightly less brilliant and strong meat tissue; fresh odor and specific type less; and texture slightly soft and slightly less elastic. The TPC value of skipjack meat slices can be maintained up to 10 hours of immersion in the solution of mangrove fruit extract Rhizopora mucronate with pH being acidic. Conclusion: The study concludes that the optimal soaking time for skipjack in Rhizophora mucronata fruit extract solution is 10 hours, as it maintains acceptable organoleptic quality, a fresh odor, and a firm texture while effectively inhibiting bacterial growth. The TPC value remains stable up to 10 hours of soaking, with an acidic pH indicating preservation effectiveness. Novelty/Originality of this article: This research introduces the use of Rhizophora mucronata fruit extract as a natural preservative for skipjack, highlighting its antimicrobial properties and potential for extending fish shelf life. The findings provide new insights into sustainable fish preservation methods using natural additives, contributing to the development of eco-friendly post-harvest technologies in fisheries.